Utilização de agregados de rochas calcárias em misturas asfálticas usinadas a quente - Assis, Sérgio Ricardo Honório de (2015)
The growing demand for aggregates in asphaltic surface course infrastructure makes necessary to research new materials, with emphasis on local materials to minimize environmental impacts and transport costs. In this way, the objective was to evaluate the use of limestone aggregates in asphalt mixtures for surface course, with substitutions of granite crusher dust (mix C2) and inclusion of limestone mineral filler (mix C3), through laboratory tests of mechanical performance. The results carried out were compared with the reference asphalt mixture (mix C1), composed of granite aggregates, and with the specifications according to DNIT 031/2006 – ES and others studies. The materials used were granite (in grading of 19 mm, 12 mm and crusher dust) and limestone aggregates (in grading of 19 mm, 12 mm, crusher dust and mineral filler), and PEN 50/70 asphalt binder. The characterization of aggregates was performed by sieve analysis, abrasion Los Angeles, absorption, density and sodium sulfate soundness test. The characterization of the asphalt binder was made by Rotational viscosity test, among others. The Marshall mix design method was used to compact asphalt mixtures and to determine optimum asphalt binder contents. Afterwards, the samples were compacted by Marshall and Superpave designs in order to check the influence of compression type on the mechanical performance. The mechanicals tests applied were indirect tensile-strenght, resilient modulus, moisture susceptibility and Flow Number. From the results, it was found that mixtures were within the specification limits. The C2 and C3 mixtures showed better mechanical behavior than the C1 mix. The addition of limestone contributed for stiffness of the mixtures and gain of mechanical resistance, mainly to permanent deformation. Regarding to moisture susceptibility, it was observed that all mixtures were susceptible to water, which implies the need to use additives. In this way, it can be concluded that hot mix asphalts produced with limestone aggregates are technically viable for use in surface courses.